2022
DOI: 10.1007/s42113-022-00128-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving Human Decision-making by Discovering Efficient Strategies for Hierarchical Planning

Abstract: To make good decisions in the real world, people need efficient planning strategies because their computational resources are limited. Knowing which planning strategies would work best for people in different situations would be very useful for understanding and improving human decision-making. Our ability to compute those strategies used to be limited to very small and very simple planning tasks. Here, we introduce a cognitively inspired reinforcement learning method that can overcome this limitation by explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Recent work proposed that artificial intelligence can provide a more scalable solution. The basic idea is to combine machine learning and educational software to automatically derive useful decision strategies from descriptions of the decisions people have to make in the real world, and then teach them at scale (Callaway et al, 2022a;Consul et al, 2022;Skirzyński et al, 2021). The method introduced in this article addresses a crucial challenge for this approach, namely the standard methods' sensitivity to the inevitable inaccuracies of our models of the real world.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent work proposed that artificial intelligence can provide a more scalable solution. The basic idea is to combine machine learning and educational software to automatically derive useful decision strategies from descriptions of the decisions people have to make in the real world, and then teach them at scale (Callaway et al, 2022a;Consul et al, 2022;Skirzyński et al, 2021). The method introduced in this article addresses a crucial challenge for this approach, namely the standard methods' sensitivity to the inevitable inaccuracies of our models of the real world.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that automatic strategy discovery can be used to improve human decision-making if the discovered strategies are well-adapted to the real-world situations where people might use them. Finally, Consul et al (2022) found Fig. 3 Illustration of the Mouselab-MDP paradigm.…”
Section: Intelligent Cognitive Tutorsmentioning
confidence: 98%
See 3 more Smart Citations